ZONING AS AN ENVIRONMENT HETEROGENEITY INTRODUCTION MECHANISM IN MANAGING TERRITORIAL EDUCATIONAL SYSTEMS DEVELOPMENT - V. Savvinov (Вестник Северо-Кавказского федерального университета, 2022)
During growing uncertainty and diversity, the environment acts as a factor influencing the processes in the educational system, and as a space for transformative activities of education management bodies. The education system itself acquires the properties of the environment, and therefore heterogeneity becomes one of its main characteristics. The article discovers the challenge of using zoning in managing territorial education systems development. The article identifies main seven groups of territorial education systems of Yakutia using the analysis of natural, social and economic, ethnolinguistic, demographic, economic and other environmental factors, considering the existing experience of zoning. It also assesses the impact ogm m heterogeneity of the environment on their development based on a comparative analysis and identifies neral and speciic features for each group of education systems.